Insulin‐like growth factor 1 and metabolic parameters are associated with nonalcoholic fatty liver disease in obese children and adolescents. (February 2017) - Liang, Shuang; Cheng, Xiangdeng; Hu, Yanyan; Song, Ruxin; Li, Guimei
Abstract: Aim: Few studies have investigated the relationship between paediatric nonalcoholic fatty liver disease (NAFLD) and insulin‐like growth factor 1 (IGF‐1). This study, carried out from July 2013 to September 2015, aimed to fill the gap and added metabolic parameters to the analysis. Methods: This was a cross‐sectional study of 168 obese children and adolescents (84% male), divided into two groups based on the presence (n = 90) or absence (n = 78) of NAFLD. All participants underwent clinical examinations, anthropometric and laboratory examinations and liver ultrasonography. Results: Nonalcoholic fatty liver disease patients had significantly lower IGF‐1 standard deviation score (IGF‐1 SDS) and higher body mass index (BMI), homeostasis model assessment of insulin resistance (HOMA‐IR) and uric acid levels than the control group. The prevalence rate of NAFLD was negatively correlated with the IGF‐1 SDS. IGF‐1 SDS was negatively associated with NAFLD, while BMI, HOMA‐IR and uric acid were positively associated with NAFLD. The combined analysis of the area under the receiver operating characteristic curve for multiple variables, including IGF‐1 SDS, BMI, HOMA‐IR and uric acid, was 0.812, with a sensitivity of 78.89% and specificity of 74.36%. Conclusion: IGF‐1, BMI, HOMA‐IR and uric acid were useful markers of NAFLD in obese children and adolescents.